Evaluation of the Urine Albumin-to-Creatinine Ratio (UAC) for Early Renal Disease: A Large-Scale Clinical Study in Cats - Cha, Ye-Eun; Lee, Soo-Yeol; Kang, Min-Hee; Kang, Hyun-Min; Kang, Dong-Jae; Park, Hee-Myung (Animals (Basel), 2025)
CKD is a leading cause of illness in older cats, but early detection is challenging due to the limitations of conventional biomarkers. This study evaluated the clinical utility of the UAC for identifying early-stage renal dysfunction in cats and proposed a diagnostic matrix incorporating the UAC with other biomarkers. Blood and urine samples from 59 healthy cats and 190 cats with CKD were analyzed, and UAC levels were compared with symmetric dimethylarginine (SDMA), creatinine, and blood urea nitrogen (BUN). UAC values were significantly elevated in cats with CKD, including those in stage 1. Receiver operating characteristic analysis identified a UAC cut-off of 16.3 mg/g, yielding 100% specificity and 43.7% sensitivity for early-stage CKD classification. The UAC showed significant correlations with other renal biomarkers and was incorporated into a multi-parameter matrix to support disease staging. These findings suggest that the UAC may be a promising supplementary biomarker for evaluating renal function in cats and could aid clinical decision-making when interpreted in conjunction with established diagnostic parameters.